1968
DOI: 10.1080/00288233.1968.10422409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of pea leaf-roll (top-yellows) virus resistance inPisum sativum

Abstract: Six pea cultivars and their Fl and F2 progenies were assessed for resistance to pea leaf-roll (top-yellows) virus infection under natural epidemic conditions. Two cultivars were highly resistant, two moderately resistant, and two highly susceptible; all Fl and the majority of F2 hybrids between any two cultivars showed a lower mean resistance than the better of the two parents. Resistance to infection was controlled by an additive system of inheritance, with "moderate" resistance being dominant to both suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…van Leur, Kumari, et al (2013) quantified BLRV resistance in Australian pea cultivars, but did not find immunity. Crampton and Watts (1968) in New Zealand concluded that resistance to pea leaf-roll/top-yellows (likely a combination of BWYV and SbDV) was based on additive and dominant genes.…”
Section: Resistance To Luteo- Polero- and Nanovirusesmentioning
confidence: 99%
“…van Leur, Kumari, et al (2013) quantified BLRV resistance in Australian pea cultivars, but did not find immunity. Crampton and Watts (1968) in New Zealand concluded that resistance to pea leaf-roll/top-yellows (likely a combination of BWYV and SbDV) was based on additive and dominant genes.…”
Section: Resistance To Luteo- Polero- and Nanovirusesmentioning
confidence: 99%
“…Results of pea luteovirus resistance studies with peas were reported simultaneously by Drijfhout (1968) and Crampton and Watts (1968). Results reported by Wilson and Close (1973), Grylls and Peak (1969), and Johnstone and Duffus (1984) suggest that Crampton and Watts probably described resistance to either (or both) beet western yellows or subterranean clover redleaf luteoviruses.…”
mentioning
confidence: 85%
“…728 variations in segregation ratios were noted. From segregation ratios of field-inoculated breeding progenies, Crampton and Watts (1968) concluded that resistance to "pea leaf-roll virus" (probably luteovirus complex) infection "was controlled by an additive system of inheritance, with moderate resistance being dominant to both susceptibility and high resistance".…”
mentioning
confidence: 99%
“…Both Drijfhout (1968) in the Netherlands and Baggett & Hampton (1991) in the USA concluded that the resistance was based on a single recessive gene, but commented on the difficulties in distinguishing between resistant and susceptible segregants. Crampton & Watts (1968) in New Zealand on the other hand concluded that resistance to pea leaf-roll (top-yellows) was based on additive and dominant genes. Wilson (1968) described studies of the vectors on 'pea leaf roll virus' in New Zealand, but did not confirm the identity of the causal organism with serology.…”
Section: Discussionmentioning
confidence: 99%